Noise and Error in Contemporary Technoculture : An Interview with Peter Krapp - Luersen, Eduardo Harry; Maschke, Guilherme Malo (My University, 2019)
The following article is an interview with Peter Krapp (UCI), conducted due to his participation as a lecturer in the 16th Week of Image. Peter Krapp is a Full Professor in the Department of Film & Media Studies at the University of California, Irvine. Before Irvine, Krapp taught at the University of Minnesota and Bard College. He has also been a Visiting Professor in South Africa, Taiwan, Brazil and across the United States. His lectures and seminars cover various topics, such as secrecy, archiving, computer games, digital culture, media theory and media arts. He edited and organized two books, Medium Cool (2002) and The Handbook Language-Culture Communication (2013), and is the author of Déjà Vu: Aberrations of Cultural Memory (2004) and Noise Channels: Glitch and Error in Digital Culture (2011). In his most recent book, Krapp maps a variety of glitches, bugs and lags that swarm the aesthetics of digital culture. At the heart of this work, he re-examines information theory and the history of design to address the creative expressions related to noisy phenomena in current forms of human-computer interaction. In our questioning, we approached Krapp to discuss themes such as the ergonomic principles that play a central role in the infrastructural development of graphical user interfaces, the aestheticization of error in digital culture, and the unstable relationship between noise ratio and technological conditions in digital music production.
Keywords: 300